Ultrasound evidence of altered lumbar fascia in patients with low back pain. Issue 1 (24th October 2022) - Tamartash, Hassan; Bahrpeyma, Farid; Mokhtari Dizaji, Manijhe
Abstract: Different hypotheses have been proposed about the role of lumbar connective tissue in low back pain (LBP). However, none of the previous studies have examined the change in the elastic behavior of lumbar fascia in patients with LBP. The present study aimed to evaluate the changes in the elastic behavior of lumbar fascia in patients with chronic non‐specific LBP based on ultrasound imaging. The sonographic strain imaging assessed the thoracolumbar fascia (TLF) of 131 human subjects (68 LBP and 63 non‐LBP). Assessments were done at L2–L3 and L4–L5 levels bilaterally. The points were located 2 cm lateral to the midpoint of the interspinous ligament. There were no significant differences in age, sex, and BMI between LBP and healthy individuals. There is a strong inverse relationship between pain severity ( r  = −0.76, n  = 68, p  = 0.004) and the TLF elastic modulus coefficient. No significant relationship were observed between age ( r  = 0.053, n  = 68, p  = 0.600), BMI ( r  = −0.45, n  = 68, p  = 0.092), and gender ( r  = −0.09, n  = 68, p  = 0.231) with the TLF elasticity coefficient. The LBP group had a 25%–30% lower TLF elastic modulus coefficient than healthy individuals. The present study is the first to evaluate the elastic coefficient of TLF using the ultrasound imaging method. The study results showed that the TLF elastic coefficient in patients with LBP was reduced compared to healthy individuals and directly related to LBP severity.